Comparative Legal Analysis of Incentives for Electric Vehicle Adoption in Indonesia and Malaysia - Nurlaily, Nurlaily; Seroja, Triana Dewi; Sudirman, Lu; Silviani, Ninne Zahara; Agustini, Shenti (International Journal of Law Reconstruction, 2024)
Carbon emissions play an important role in the acceleration of climate change, which threatens the livelihoods of many people around the world. Electronic vehicles (EVs) serve as a solution to this problem by reducing the amount of pollution and enabling the use of renewable energy as a source. This research analyzes the incentives provided by countries that are trying to reduce their carbon emissions with EVs, namely Indonesia and Malaysia. The analysis is supported by a comparative legal research method and statutory approach. This research finds that Malaysia’s framework of incentives is superior to that of Indonesia’s, as incentives provided by Indonesia do not address the issue of carbon emissions entirely and are buried within a very fragmented legal framework. The research proposes a number of changes that need to be made in Indonesia to support the EV industry in all of the aspects that are relevant to its development, such as R&D, human resources, consumer support, and financial support for manufacturers.